Pathophysiological Significance of Hepatic Apoptosis. (30th December 2012) - Wang, Kewei; Lin, Bingliang
Abstract : Apoptosis is a classical pathological feature in liver diseases caused by various etiological factors such as drugs, viruses, alcohol, and cholestasis. Hepatic apoptosis and its deleterious effects exacerbate liver function as well as involvement in fibrosis/cirrhosis and carcinogenesis. An imbalance between apoptotic and antiapoptotic capabilities is a prominent characteristic of liver injury. The regulation of apoptosis and antiapoptosis can be a pivotal step in the treatment of liver diseases.